Fructose‐Derived Levan Nanoparticles Protect Against Osteoarthritis by Directly Blocking CD44 Activation. Issue 29 (26th June 2022) - Cho, Chanmi; Lee, Jin Sil; Oh, Hyeryeon; Kang, Li‐Jung; Hwang, Yiseul; Chae, Sunyoung; Lee, In‐Jeong; Kim, Seok Jung; Woo, Hyunmin; Eyun, Seong‐il; Kang, Ho Chul; Choi, Won Il; et al.
Abstract: Although the development of several inflammatory diseases can be initiated in response to CD44 receptor signaling dysregulation, anti‐CD44 antibody therapy has been discontinued in clinical trials owing to its severe adverse effects. Moreover, biocompatible materials that block CD44 are unknown. Here, self‐assembled levan nanoparticles (LevNPs) through simple nanoprecipitation without chemical conjugation of biocompatible levan are developed. LevNPs are prepared through a simple nanoprecipitation without chemical conjugation; this results in particles with a consistently dispersed hydrodynamic diameter of approximately 230 nm. The physicochemical properties of LevNP are well‐maintained even after long‐term storage in a physiological buffer, suggesting that LevNPs are stable and useful for various biomedical applications. A protein array and an in silico LevNP‐CD44 interaction assay reveal that LevNPs specifically bind to CD44. Importantly, CD44 is highly expressed in the cartilage of patients with osteoarthritis (OA). LevNPs showed no cytotoxicity and reduced catabolic factor expression in an OA mimic in vitro. Furthermore, intra‐articular injection of LevNPs exhibited long‐term retention ability in the knee joint and protection against posttraumatic OA cartilage destruction in mice with medial meniscus destabilization–induced OA. These results show that LevNPs are biocompatible and exhibit potential as a nanotherapeutic for protecting against OA pathogenesis by directly blocking CD44. Abstract : Fructose‐derived levan nanoparticles are developed as anti‐inflammatory nanotherapeutic agents, which are biocompatible materials. They are found to be effective as anti‐inflammatory agents by blocking CD44 activation through an interaction with the N‐terminal CD44 sequence and LevNP. These particles can be used to alleviate inflammatory osteoarthritis and may be applicable for treating various inflammatory diseases.